2018
DOI: 10.1038/s41534-018-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantum simulation of photosynthetic light harvesting

Abstract: Near-unity energy transfer efficiency has been widely observed in natural photosynthetic complexes. This phenomenon has attracted broad interest from different fields, such as physics, biology, chemistry, and material science, as it may offer valuable insights into efficient solar-energy harvesting. Recently, quantum coherent effects have been discovered in photosynthetic light harvesting, and their potential role on energy transfer has seen the heated debate. Here, we perform an experimental quantum simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 42 publications
0
84
0
2
Order By: Relevance
“…According to the study in ref. [] in this case the hierarchical equation of motion (HEOM) can treat the quantum open system in a unified way, which has recently been experimentally verified using nuclear magnetic resonance (NMR) . In this demonstration, the HEOM was exponentially accelerated by a specific mapping algorithm.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…According to the study in ref. [] in this case the hierarchical equation of motion (HEOM) can treat the quantum open system in a unified way, which has recently been experimentally verified using nuclear magnetic resonance (NMR) . In this demonstration, the HEOM was exponentially accelerated by a specific mapping algorithm.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…Two-photon entangled states and single-photon states are used as the information carriers in our protocol, they can be prepared and controlled [47,48,49,50,51] even at a great distance. And photon states are also of great use in other fields, such as quantum computation [52,53,54,55] and quantum simulation [56,57]. We utilize the Bell measurement to deduce the final secret key.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Figure 1 shows some examples of platforms where single-excitation stochastic networks have been successfully implemented, namely optical tweezers [25], waveguide arrays [24], superconducting circuits [26][27][28], and electrical-circuit arrays [29]. Quite recently, it has been shown that stochastic quantum networks can also be implemented in fascinating platforms, such as nuclear magnetic resonance systems [30], and ion traps [31,32].…”
Section: Single-particle Dynamicsmentioning
confidence: 99%